RESISTÊNCIA DE GENÓTIPOS DE MILHO PIPOCA A DOENÇAS - Fantin, Gisèle Maria; Dudienas, Christina; Castro, Jairo Lopes de; Sordi, Guido de (REVISTA DE AGRICULTURA, 2015)
RESISTÊNCIA DE GENÓTIPOS DE MILHO PIPOCA A DOENÇAS